PENGEMBANGAN PROFESI BERKELANJUTAN : UPAYA PENINGKATAN PROFESIONALISME GURU - Nazaruddin Ali Basyah (Majelis Pendidikan Aceh, 2022)
This study reviewed the effects of the government's efforts to continue to develop the teaching profession as a strong and equal profession with other professions. The study aims to identify the government has made efforts to improve teacher professionalism, including increasing qualifications and higher educational requirements for teaching staff from the school level to tertiary institutions. This study uses a qualitative method using a descriptive approach and document analysis. The results of this study try to reveal, analyze, and deal with words as the main tool to give meaning to the research data of the teaching profession program. Teachers are professional positions, therefore teachers must be professional. A number of studies have proven that professional teachers are one of the important indicators of quality schools. Thus, the development of the teaching profession needs to be carried out. Teacher professional development is a process to assist teachers in doing their job effectively and efficiently.